1989
DOI: 10.1139/f89-087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forest Harvesting on Spawning Gravel and Incubation Survival of Chum (Oncorhynchus keta) and Coho Salmon (O. kisutch) in Carnation Creek, British Columbia

Abstract: Following logging, pea gravel and sand (i.e. fines) in the stream bed of Carnation Creek, British Columbia increased 4.6 and 5.7%, respectively. The quantity of fines was greater in the bottom layer, while the frequency and magnitude of changes in composition were greater in the top layer of streambed cores. Changes in streambed fines depended on the timing and type of streamside logging and on the timing of large freshets. Accumulating fines appeared to originate from erosion of streambanks or from upstream s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 13 publications
1
96
0
1
Order By: Relevance
“…Previous studies have demonstrated that reduced emergence success from high sedimentation can result in low juvenile densities and low adult recruitment (Cederholm andReid 1987, Scrivener andBrownlee 1989). Of the 6 sites where high levels of small or coarse fines were recorded, only the sites located in the mainstem of Lake Creek showed supporting evidence for low recruitment.…”
Section: Is Fine Sediment Limiting Recruitment?mentioning
confidence: 80%
“…Previous studies have demonstrated that reduced emergence success from high sedimentation can result in low juvenile densities and low adult recruitment (Cederholm andReid 1987, Scrivener andBrownlee 1989). Of the 6 sites where high levels of small or coarse fines were recorded, only the sites located in the mainstem of Lake Creek showed supporting evidence for low recruitment.…”
Section: Is Fine Sediment Limiting Recruitment?mentioning
confidence: 80%
“…La morphologie particulière de la frayère (une dépression suivie d'un dôme), qui favorise la pénétration de l'eau dans le substrat (VAUX, 1962), est progressivement nivelée par les crues, ce qui limite ce processus. De plus, les sédiments fins qui pénètrent dans le substrat à ces occasions réduisent la circulation interstitielle de l'eau et les apports d'oxygène en provenance de l'eau de surface (VAUX, 1962 ;BESCHTA et JACKSON, 1979 ;SCRIVENER et BROWNLEE, 1989).…”
Section: Qualité De L'eau Interstitielleunclassified
“…Management actions however, can have multiple impacts. For example, timber harvest can increase peak streamflows, increasing the mortality of young fishes (Scrivener and Anderson 1984), and can also increase streambed sediment, decreasing salmonid spawning success (Scrivener and Brownlee 1989).…”
Section: Introductionmentioning
confidence: 99%